Mapping protein dynamics in catalytic intermediates of the redox-driven proton pump cytochrome c oxidase - Busenlehner, Laura S. (National Academy of Sciences, 2006)
Redox-driven proton pumps such as cytochrome c oxidase (CcO) are fundamental elements of the energy transduction machinery in biological systems. CcO is an integral membrane protein that acts as the terminal electron acceptor in respiratory chains of aerobic organisms, catalyzing the four-electron reduction of O(2) to H(2)O. This reduction also requires four protons taken from the cytosolic or negative side of the membrane, with an additional uptake of four protons that are pumped across the membrane. Therefore, the proton pump must embody a “gate,” which provides alternating access of protons to one or the other side of the membrane but never both sides simultaneously. However, the exact mechanism of proton translocation through CcO remains unknown at the molecular level. Understanding pump function requires knowledge of the nature and location of these structural changes that is often difficult to access with crystallography or NMR spectroscopy. In this paper, we demonstrate, with amide hydrogen/deuterium exchange MS, that transitions between catalytic intermediates in CcO are orchestrated with opening and closing of specific proton pathways, providing an alternating access for protons to the two sides of the membrane. An analysis of these results in the framework of the 3D structure of CcO indicate the spatial location of a gate, which controls the unidirectional proton flux through the enzyme and points to a mechanism by which CcO energetically couples electron transfer to proton translocation.